Statistical analyses for NANOGrav 5-year timing residuals. (February 2017) - Wang, Yan; Cordes, James M.; Jenet, Fredrick A.; Chatterjee, Shami; Demorest, Paul B.; Dolch, Timothy; Ellis, Justin A.; Lam, Michael T.; Madison, Dustin R.; McLaughlin, Maura A.; Perrodin, Delphine; Rankin, Joanna; et al.
Abstract: In pulsar timing, timing residuals are the differences between the observed times of arrival and predictions from the timing model. A comprehensive timing model will produce featureless residuals, which are presumably composed of dominating noise and weak physical effects excluded from the timing model (e.g. gravitational waves). In order to apply optimal statistical methods for detecting weak gravitational wave signals, we need to know the statistical properties of noise components in the residuals. In this paper we utilize a variety of non-parametric statistical tests to analyze the whiteness and Gaussianity of the North American Nanohertz Observatory for Gravitational Waves (NANOGrav) 5-year timing data, which are obtained from Arecibo Observatory and Green Bank Telescope from 2005 to 2010. We find that most of the data are consistent with white noise; many data deviate from Gaussianity at different levels, nevertheless, removing outliers in some pulsars will mitigate the deviations.